FANTASIA AS THE MAIN WAY OF MANIFESTING PERSONALITY CONSTRUCTS IN THE METHOD OF PSYCHOTHERAPY «I-RECONSTRUCTION» - Pavlenko, Tetyana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The concept of «construct» is proposed and defined in the article. The main constructs of the personality according to the method of psychotherapy «Self-reconstruction» and their manifestation in the client’s fantasies are considered.